Why People Benefit from Online Learning: Empirical Assessment from Jordan - Gharaibeh, Malik Khlaif; Gharaibeh, Natheer Khleaf (Society of Visual Informatics, 2024)
Most countries have imposed online learning on universities and schools due to the COVID-19 pandemic. These days, despite the end of the impact of the COVID-19 pandemic on the educational sector, many countries in the world are still adopting this type of education and trying to develop its methods due to the many benefits it provides. The main objective of conducting this study is to determine the main factors affecting the acceptance of online learning in Jordan. The data were analyzed using SmartPLS 4. 940 questionnaires were distributed in Irbid and Amman. The study's results supported the hypotheses, as it was found that the acceptance of e-learning is statistically and positively associated with the four variables. This study provides essential guidelines for decision-makers and those in charge of the educational process, as it supports the body of knowledge with new variables that were not used in previous studies. Online learning is considered inevitable for adoption in universities and schools, especially when looking at the benefits that institutions derive from its adoption. Saving time, effort, and costs are the most important benefits when applying online learning. This study attempted to determine the main factors affecting the acceptance of online learning in Jordan. The study's results aligned with the hypotheses that technological development, women's empowerment, disabilities, and environmental benefits significantly affect the acceptance of online learning. This study presents a new model and theoretical framework that researchers in this field can build upon.